Lexical Cohesion in Antoine de Saint-Exupéry’s The Little Prince: A Reiteration-Based Analysis - Alwaeni, Alvia; Muhid, Abdul; Sutarman; Sudewi, Ni Ketut Putri Nila; Hastuti, Hilda (Lexeme : Journal of Linguistics and Applied Linguistics, 2025)
This study investigates the use of lexical cohesion in The Little Prince, a novel by Antoine de Saint-Exupéry, using Halliday and Hasan’s (1976) theory of cohesion, with a specific focus on the reiteration category. The objectives of the study are: (1) to identify the types of lexical cohesion used by the main character, the Little Prince; and (2) to analyze how each type contributes to the textual structure and meaning of the narrative. Employing a qualitative descriptive method and discourse analysis approach, this study focuses on the odd-numbered chapters of the novel as the primary data source. The analysis reveals four types of reiteration; repetition, synonymy, antonymy, and superordinate. With repetition being the most dominant (61 occurrences). These cohesive devices are shown to significantly enhance the narrative's coherence, emotional tone, and philosophical nuance. The findings underscore the integral role of lexical cohesion in constructing the character’s voice, and they contribute to a deeper understanding of how linguistic choices support thematic and stylistic unity in literary texts..